Menstrual hygiene management practice among adolescent girls: a cross sectional study in Nepal - Gautam, Koshish Raj; Dahal, Harsha Raj; Karki, Kshitij; Acharya, Shradha; Subedi, Suraksha; Upadhyay, Abinash; Shah, Sanjeev Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Good menstrual hygiene is fundamental to health, hygiene and well-being of women and girls. As menstruation itself considered as taboo in Nepalese society, it has direct impacts on the health of the women and adolescent. The objective of the study is to assess the knowledge and practices regarding menstrual hygiene management among adolescent girls. Methods: A cross- sectional study design was conducted among 398 samples. Simple random sampling was done to select the resource center schools and probability proportionate sampling (PPS) technique used to get sample size. Structured interview schedule is used to collect data and analysed from SPSS software after validation. Results: Knowledge on menstrual hygiene management was good in urban adolescent girls (93.69%) as compared to rural (6.31%). Similarly, level of practice was good regarding menstrual hygiene management was good in urban adolescent girls (91.29%) as compared to rural (8.71%). Place of the residence and knowledge level of the adolescent girls was highly significant (p<0.001). Conclusions: The findings showed that rural adolescent girls had poor knowledge, various misconceptions and inadequate practices regarding menstrual hygiene management.